Essential demographic methods - Wachter, Kenneth W. (Cambridge, Massachusetts Harvard University Press, 2014)
"Classroom-tested over many years and filled with fresh examples, Essential Demographic Methods is tailored to beginners, advanced students, and researchers. Award-winning teacher and eminent demographer Kenneth Wachter draws on themes from the individual lifecourse, history, and global change to bring out the wider appeal of demography" -- Provided by publisher.
1. Exponential growth -- 2. Periods and cohorts -- 3. Cohort mortality -- 4. Cohort fertility -- 5. Population projection -- 6. Period fertility -- 7. Period mortality -- 8. Heterogenous risks -- 9. Marriage and family -- 10. Stable age structures -- 11. Migration and location.
Includes bibliographical references (pages 279-283) and index.
Keywords: Demography -- Statistical methods; Demography -- Mathematical models; Population -- Statistical methods; Population -- Mathematical models; Population forecasting -- Statistical methods; Population forecasting -- Mathematical models